Effects of Young Corn Ear Addition on Nutritional Composition and Acceptability of Conventional Cake - Chow, Yuh Nien; Wan Rosli, W. I. (Nutrition Society of Malaysia, 2014)
Introduction: Scientific evidence indicates that higher dietary fibre consumption protects against various chronic diseases and leads to recovery enhancement. Young corn ear is very rich in total dietary fibre (fDF). The study objective was to evaluate the effects of young corn ear addition on the nutritional composition, textural properties and sensory attributes of conventional cake. Methods: Wheat flour used in the preparation of conventional cake was substituted with different percentages (0%,5%,10% and 15%) of young corn ear powder (YCP). Moisture, total ash, fat, protein and TDF content of conventional cake samples were investigated. Textural properties including firmness, cohesiveness, springiness, gumminess and chewiness were examined. The aroma, colour, chewiness, tenderness, flavour and overall acceptance of conventional cake were evaluated via sensory evaluation. Results: The conventional cake with addition of 15% YCP recorded the highest moisture content. There was no predictable trend observed in the ash and fat content following the incorporation of YCP. Addition of 15% of YCP increased the protein content significantly while TDF content of conventional cake increased proportionally (1.42%-2.88%) with the level of YCP added. The incorporation of YCP did not produce any trend on all the textural properties of conventional cake. Conventional cake with 10% of YCP was the most preferred manifested by the highest scores in chewiness, tenderness and flavour attributes. Conclusion: In conclusion, 10% of YCP could be recommended as the ideal formulation in order to produce a healthier conventional cake without jeopardising acceptability.